Hubungan Kesepian dengan Problematic Internet Use pada Emerging Adulthood di Masa Pandemi - Rizka Putri Ramadhani; Siti Qodariah (UNISBA Press, 2022)
Abstract. During the Covid-19 pandemic, internet usage has increased significantly. Internet use among emerging adulthood has many negative effects because of its excessive use, such as feeling comfortable when interacting online, and having difficulty controlling oneself when accessing the internet. Internet use is also used to help cope with negative mood states, such as loneliness. Loneliness according to Russell, (1996) is a subjective feeling that results from dramatic changes in social life where there is no intimacy in a relationship. is a negative feeling experienced by a person due to an unpleasant situation from a feeling that does not match the expected social relationship. The purpose of this study was to obtain empirical data on the relationship between loneliness and problematic internet use in emerging adulthood during the COVID-19 pandemic. This study uses the correlational method with the research subjects totaling 349 respondents who were selected using accidental sampling techniques. Data collection uses the UCLA Loneliness scale version 3 developed by Russell, DW (1996) and the problematic internet use scale, namely the Generalized Problematic Internet Use Scale 2 (GPIUS 2) developed by Caplan (2010). Data analysis using Pearson correlation test. The results showed that there was a significant positive relationship between loneliness and problematic internet use (p = 0.000 < 0.05) by obtaining a correlation coefficient of 0.259 with a low but definite level of closeness. Abstrak. Selama pandemi Covid-19, penggunaan internet mengalami peningkatan yang signifikan. Penggunaan internet di kalangan emerging adulthood memberikan banyak efek negatif karena penggunaannya secara berlebihan, seperti merasa nyaman ketika berinteraksi secara online, dan kesulitan mengontrol diri ketika mengakses internet. Penggunaan internet juga digunakan untuk membantu mengatasi keadaan suasan hati yang negatif, seperti kesepian. Kesepian menurut Russel, (1996) adalah perasaan subyektif yang dihasilkan dari perubahan dramatis dalam kehidupan sosial dimana tidak ada keintiman dalam suatu hubungan. adalah perasaan negatif yang dialami seseorang dikarenakan situasi yang tidak menyenangkan dari adanya perasaan yang tidak sesuai antara hubungan sosial dengan yang diharapkan. Tujuan dari penelitian ini adalah untuk mendapatkan data empiris mengenai hubungan kesepian dengan problematic internet use pada emerging adulthood di masa pandemi covid-19. Penelitian ini menggunakan metode korelasional dengan subjek penelitian berjumlah 349 responden yang diseleksi menggunakan teknik pengambilan sampling aksidental. Pengumpulan data menggunakan UCLA Loneliness scale version 3 yang dikembangkan oleh Russel, DW (1996) dan skala problematic internet use yaitu Generalized Problematic Internet Use Scale 2 (GPIUS 2) yang dikembangkan oleh Caplan (2010). Analisa data menggunakan uji korelasi pearson. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara kesepian dengan problematic internet use (p=0.000< 0.05) dengan memperoleh nilai koefesien korelasi sebesar 0,259 dengan tingkat keeratan rendah tapi pasti.